Fly ash–GGBS geopolymer in boron environment: A study on rheology and microstructure by ATR FT-IR and MAS NMR. (18th January 2021) - Revathi, T.; Jeyalakshmi, R.
Graphical abstract: Highlights: Borax within the threshold range increases performance of the resulting geopolymer. The retarding effect of borax originates from the compensatory role of [BO4 ] in [AlO4 ]. Surface chemistry governs the rheological parameters of the fly ash–GGBS matrix. The structural framework of the geopolymer was studied by ATR-FT-IR and MAS NMR ( 29 Si, 27 Al, 11 B). Transformation of non-polymerized silica (Q 0 ) to more polymerized Q 3 /Q 4 has been confirmed. Abstract: The present study focuses on the use of borax composite sodium silicate activator (B) in place of water glass (S) in the fly ash–GGBS composite (4:1) geopolymerization. The substituent is favoured as it delivers advantages such as increased setting time and workability by mitigating the agglomeration of flocks without affecting the compressive strength of the geopolymer. Microstructural changes of boroaluminosilicate were studied with the help of ATR-FT-IR and MAS NMR. Rheology studies indicated that the borax composite pastes display shear thinning behaviour with low yield stress and fit well with the Bingham model. In-situ ATR-FT-IR spectrum revealed the severing of silica bonds by soluble [BO4 ] and its incorporation into the silicate backbone resulted in the drop in of Si–O–T asymmetry vibration response. The NMR spectral changes of 29 Si, 27 Al and 11 B nuclei environment in geopolymeric tetrahedral network showed that the fraction of [SiO4 ] and [BO4 ] increases upon borax addition with the diminished fraction of B 3 non-rings without any specific changes in Al coordination. The tetrahedral boron absorption band in the wave numbers at 1380–1310 cm −1 and1134 cm –1 is observed in FT-IR and its configuration is compatible in the reaction product.